Analisis Pengaruh Pendidikan, Upah Minimum, dan Tingkat Pengangguran Terbuka terhadap Tingkat Kemiskinan di Kota Banjarbaru Tahun 2011-2020 - Harira, Farda Kirana; Siregar, Syahrituah (PPJP ULM, 2023)
The purpose of this study is to analyze the effect of education on poverty in the city of Banjarbaru, analyze the impact of the minimum wage on poverty in the town of Banjarbaru, analyze the development of the open unemployment rate on poverty in the city of Banjarbaru. This study uses multiple linear regression analysis with the independent variables Education (X1), Minimum Wage (X2), and Unemployment Rate (X3) on the dependent variable Poverty Level (Y1). This study indicates that the education variable did not significantly affect poverty in Banjarbaru City from 2011 to 2020. This is evidenced by the t-test, which produces a regression value of -0,018 with a significance value of 0.896. The independent variable minimum wage did not significantly affect poverty in Banjarbaru City from 2011 to 2020. This is evidenced by the t-test, which produces a regression value of -2.326 with a significance value of 0.059. The independent variable, the open unemployment rate, significantly affected poverty in Banjarbaru City from 2011 to 2020. This is evidenced by the t-test, which produces a regression value of 2.912 with a significance value of 0.027.